2015
DOI: 10.1002/ejic.201500070
|View full text |Cite
|
Sign up to set email alerts
|

A Copper Porphyrin for Sensing H2S in Aqueous Solution via a “Coordinative‐Based” Approach

Abstract: A "turn on" fluorescence-based probe for sensing H 2 S in water via a coordinative-based approach has been successfully devised. The probe can selectively detect H 2 S in aqueous solutions over other anions, biothiols, and common

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…In contrast, when exciting a solution of py‐cyclam‐pyr‐Cu at the same wavelength, an immediate and visible quenching of the py‐cyclam‐pyr fluorescence is registered (see Figure ). Most likely, the quenching is due to the coordination of paramagnetic Cu 2+ to the free ligand, as already reported for different copper complexes , , , , , , , . The fluorescence intensity of the resulting py‐cyclam‐pyr‐Cu system remained stable for a week, thus suggesting stability of the construct over this period.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…In contrast, when exciting a solution of py‐cyclam‐pyr‐Cu at the same wavelength, an immediate and visible quenching of the py‐cyclam‐pyr fluorescence is registered (see Figure ). Most likely, the quenching is due to the coordination of paramagnetic Cu 2+ to the free ligand, as already reported for different copper complexes , , , , , , , . The fluorescence intensity of the resulting py‐cyclam‐pyr‐Cu system remained stable for a week, thus suggesting stability of the construct over this period.…”
Section: Resultssupporting
confidence: 67%
“…The majority of the copper complexes reported in the literature as H 2 S sensors harness the displacement of the metal from the fluorophores' environment to generally produce fluorescence turn‐on changes by the H 2 S‐mediated precipitation of metal sulfides , , , , , , . In contrast, in 2015, our research group reported a simple copper porphyrin complex as a “turn‐on” fluorescent probe for the detection of H 2 S in aqueous media, in which the sensing mechanism was based on binding HS – to the copper center …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TCPP as fluorescence emitter is covalently attached to the AuNR surface with controllable silica shell thickness, resulting in the significant enhancement of fluorescence intensity via plasmon–exciton coupling. Cu 2+ is a well‐known highly efficient fluorescent quencher due to its paramagnetic properties via electron or energy transfer, and as a result the copper porphyrin (TCPP‐Cu 2+ ) has a weak fluorescence . Upon the introduction of PPi, the strong affinity between Cu 2+ and PPi can promote the disassembly of the turn‐off state of TCPP‐Cu 2+ complexes, and the process can be observed by monitoring the fluorescence recovery of TCPP (Scheme B).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Additional metal-centered reactions may also be observed for porphyrins with transition metal ions, the most studied of which have been the M II /M III processes involving porphyrins with Fe, Co, Ni or Mn centers. 1,2,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Our recent report of a Cu II /Cu III porphyrin oxidation involved highly substituted nonplanar compounds 12 and we wished to know how changing the planarity or p-ring system of the porphyrin macrocycle by addition of four b,b 0fused butano or benzo groups might affect the redox potentials and electron transfer mechanisms of these copper(II) porphyrins. 1,2 A number of meso and/or b-substituted copper porphyrins have been synthesized and characterized as to their spectroscopic properties and electrochemistry 1,2,12,13 and these synthetic copper porphyrins have been the subject of numerous investigations.…”
Section: Introductionmentioning
confidence: 99%